Maternal practice of exclusive breastfeeding on 0-6 month’s infants' health outcomes in Bayelsa West, Nigeria - G. E. Emily Kiridi; Solomon M. Uvoh; Charles N. Ngaikedi (Research Journal of Food Science and Nutrition, 2026)
This study assessed the physiological impact and prevalence of exclusive breastfeeding practice among mothers of infants of 0-6months in SALGA of Bayelsa State. A cross-sectional survey design using a multistage sampling technique was employed to select all 315 mothers with infants of 0-6months that met the criteria for the study out of 325 structured questionnaires (main instrument used) dispatched. The results show that 20-29yrs (36.2%) make up the largest share of the considered population, while those with tertiary education (51.4%) dominate, followed by those with a secondary certificate (43.8%). The mothers of the infants were mostly (53.3%) married. The outcome from this study shows 23.8% of mothers are practicing exclusive breastfeeding compared to 76.2% who have introduced supplementary food to their infants’ diets. Most infants (51.4%) have experienced fever within six months interval compared to 12.4% with no major signs of illness. Lack of time due to work was a major barrier (39.0%) for mothers to practice EBF. The study further observed that health care providers (56.2%) are playing a key role in educating mothers (100%) on the Physiological importance of exclusive breastfeeding. Support from healthcare providers and health education will play a significant role in encouraging mothers to practice exclusive breastfeeding. Interventions addressing work-related time constraints, including breastfeeding-friendly workplace policies and maternity protection, may help improve exclusive breastfeeding practices among working mothers. Also, the study reported health problems among the infants; further analytical or longitudinal research is needed to determine their relationship with EBF.